Innovative China: R&D subsidies, patent measures, and productivity - Philipp Boeing (ZEW - Leibniz Centre for European Economic Research, 2020)
The forthcoming fourteenth Five-Year Plan (2021-2025) emphasizes innovation as the driving force to double China's GDP and income per capita until the year 2035, implying five percent annual output growth. China's innovative and economic performance, however, is less outstanding than often perceived, and there is still a long way before it reaches the status of a high-income country. Government intervention, either through subsidies or state ownership of firms, has often resulted in poor outcomes, when compared with market-based alternatives. In other words, market-oriented reforms have been more important to economic performance than subsequent government intervention in these markets. Notwithstanding China's substantial increase in innovation activity, productivity growth in the overall economy and manufacturing industries fell by half or more than half after the global financial crisis. Moreover, efficiency gains appeared largely within incumbent firms, whereas typical productivity gains from entry, exit or reallocation diminished or turned negative because of policy distortions. While China's increasing innovation efforts may have prevented an even more severe productivity decline, returns to catching-up oriented R&D are diminishing, as China is closing in on its distance on the global knowledge frontier. At the same time, China faces more political restrictions abroad in accessing foreign cutting-edge technology. The increasingly inward-looking and mission-driven nature of Chinese innovation policy suggests that research productivity might continue to decline faster in China than elsewhere. Innovation policy, in general, may contribute to diminishing research productivity if additional R&D has lower economic returns than privately funded projects. Explicitly mission-driven policy may be even more harmful if government-supported technologies that contribute to strategic government purposes, such as national security, turn out to be economically inferior compared to the choice of the market. While China's innovation policy often addresses cutting-edge innovation and prestige projects, the desire to leap frog and move into radically new products and technologies may come at huge opportunity costs. In other words, results may be occasional Sputnik moments in galaxies of mediocracy. (...)
Keywords: 330